RARE-EARTH ELEMENTS AND THE GENESIS OF ORE MINERALIZATION AT THE KALGUTINSKOE TUNGSTEN ORE FIELD, GORNYI ALTAI - Ivanova G.F.; Kolesov G.M.; Karpukhina V.S.; Cherkasova E.V. (My University, 2006)
Rare-earth elements (REE) are widely used as indicators of the conditions under which rocks and minerals were produced. This paper reports the results of our study of REE in granites and minerals from quartz zones with ore mineralization and the principal parameters under which these minerals were formed at the Kalgutinskoe ore field, which is located in the south-eastern part of the Gornyi Altai Range, within the Charysh–Terekta tectono–stratigraphic zone.
Keywords: Kalgutinskoe ore field; Gornyi Altai